Trans-Oral Incisionless Fundoplication (TIF). Issue 2 (June 2021) - Chang, Kenneth J.
Transoral Incisionless Fundoplication (TIF) is designed to create a 3 cm length, 270° to 300°, omega-shaped flap valve, reconstructing the structure and function of the lower esophageal sphincter (LES), including the gastric sling fibers. As such, TIF is a treatment option for GERD patients with an intact crura, but have lost the integrity and function of the LES. In patients requiring a hernia repair, TIF can be used concomitantly (cTIF). While there are a number of steps to the TIF 2.0 procedure, many of the sequences are repetitive and follow a standardized protocol, optimizing efficiency, safety, and scalability.